A spatial vascular transcriptomic, proteomic, and phosphoproteomic atlas unveils an angiocrine Tie-Wnt signaling axis in the liver - Inverso, Donato; Shi, Jingjing; Lee, Ki Hong; Jakab, Moritz; Ben-Moshe, Shani; Kulkarni, Shubhada; Schneider, Martin; Wang, Guanxiong; Komeili, Marziyeh; Argos Vélez, Paula; Riedel, Maria; Spegg, Carleen; et al. (Developmental cell, 2021)
Single-cell transcriptomics (scRNA-seq) has revolutionized the understanding of the spatial architecture of tissue structure and function. Advancing the “transcript-centric” view of scRNA-seq analyses is presently restricted by the limited resolution of proteomics and genome-wide techniques to analyze post-translational modifications. Here, by combining spatial cell sorting with transcriptomics and quantitative proteomics/phosphoproteomics, we established the spatially resolved proteome landscape of the liver endothelium, yielding deep mechanistic insight into zonated vascular signaling mechanisms. Phosphorylation of receptor tyrosine kinases was detected preferentially in the central vein area, resulting in an atypical enrichment of tyrosine phosphorylation. Prototypic biological validation identified Tie receptor signaling as a selective and specific regulator of vascular Wnt activity orchestrating angiocrine signaling, thereby controlling hepatocyte function during liver regeneration. Taken together, the study has yielded fundamental insight into the spatial organization of liver endothelial cell signaling. Spatial sorting may be employed as a universally adaptable strategy for multiomic analyses of scRNA-seq-defined cellular (sub)-populations.
Das PDF enthält zusätzlich einen Anhang
Gesehen am 28.05.2021